Sustainable Collaborative Governance Liman Beach Nature Tourism, South Semau District, Kupang Regency - ANDHIKA, Yutriani; NEOLAKA, Melkisedek N.B.C.; LINO, Maria Magdalena; DJAHA, Syukur M. Adang (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze collaborative governance practices in the management of sustainable local tourist destinations in Liman Beach, South Semau District. Sustainable tourism, according to the United Nations World Tourism Organization (UNWTO, 2018), considers economic, social, and environmental impacts to meet the needs of tourists and host communities. The collaborative governance model developed by Ansell and Gash (2008) is a reference in evaluating the interaction between actors in building consensus and shared responsibility. The method used is a literature study with a descriptive qualitative approach to evaluate the relationship between stakeholders and institutions that support sustainable tourism management. The results of the analysis show that although initial interaction between actors has occurred, structured and inclusive collaborative practices have not been established due to government dominance, lack of formal recognition of local communities, and lack of inclusive institutions. This study concludes that strengthening customary institutions, involvement of the private sector, and empowering local communities through deliberative forums are key in creating sustainable and equitable tourism management.